IMPLEMENTASI GERAKAN LITERASI SEKOLAH DALAM MENINGKATKAN BUDI PEKERTI SISWA DI SMK NUSANTARA JOMBANG - Desy Naelasari; Nazilatul Izza (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
Literacy is inseparable from the world of education. Literacy is a means for students to recognize, understand, and apply the knowledge they get in school. Literacy is also related to the lives of students, both at home and in the surrounding environment to foster noble character. The results of this study include: 1. The school literacy movement at SMK Nusantara is at the learning stage, namely the implementation of various strategies to understand texts in all subjects. Which is then supported by the use of physical, social, affective and academic environments accompanied by a variety of readings (print, visual, auditory, digital), which are rich in literacy outside textbooks to enrich knowledge in subjects. 2. The character of class X students in SMK Nusantara is enhanced by practicing morals towards God, towards others and the environment. 3. Implementation of the school literacy movement in improving the character of class X students at SMK Nusantara by: a. Examples or examples taken by the teacher, b. Spontaneous activity, c. Reprimand or punishment given to students who do not take part in literacy activities, d. The coding of the environment by providing a literal environment, e. Routine activities.